Učinkovitost robotsko podprte vadbe za izboljšanje funkcije roke pri otroku z okvaro osrednjega živčevja - Groleger Sršen, Katja (Rehabilitacija (Ljubljana), 2022)
Background: Several therapeutic methods are available to improve hand function in a child with hemiparetic cerebral palsy, from constraint- induced manual therapy and bimanual therapy, to the use of botulinum toxin and orthoses. Recently, robot-assisted exercise in virtual environment has also become popular. It enables a high number of repetitions of directed hand movements, which should contribute to improving function. By reviewing the literature, we wanted to check what is the age of children included in the exercise on the ArmeoSpring Pediatric device, what are their diagnoses, what is the work protocol and what tests are used to assess the improvement of hand function. Methods: We searched the PubMed database for all articles that were published until 31st January 2022 using the with keywords »child«, »arm«, »robot-supported exercise«, »Armeo« and »rehabilitation«. Additional articles were found on the manufacturer's website. Results: We found 65 articles, but only eight of them met the inclusion criteria. On the manufacturer's website, we found six additional articles, three of which were new with respect to the first search. The included children were mostly teenagers, and the younger ones were at least five or six years old. The diagnosis of cerebral palsy was predominant. Individual training on a robotic device mostly lasts up to 45 minutes, from 2 to 5 times per week, for four weeks. To assess the impact on arm function, the authors of the most recent studies mainly used the Melbourne Assessment of Unilateral Lateral Hand Function and the Quality of Upper Extremity Skills Test. The authors of the included studies confirmed the effectiveness of robot-assisted exercise. Conclusion: Training on the Armeo Spring Pediatric device is gaining ground in rehabilitation programs for children with unilateral hand dysfunction as part of cerebral palsy, as well as after traumatic brain injury and other brain impairments. The authors of most studies have reported significant improvements in arm function. Improvements were also observed in the implementation of selected objectives and satisfaction with the implementation.
Keywords: ArmeoSpring; Child; function; funkcija; hand; hemiparesis; hemipareza; otrok; rehabilitation; Robotics; robotsko podprta vadba; robot-supported exercise; roka